E-Bu Confinement Care Service (E-BuCCS) CHA Beauty Home Spa / Syazwani Nasuha Shahril - Shahril, Syazwani Nasuha (2023)
E-commerce is growing trend that starting to transfer the business operation from physical stores to digital, which is more convenient and flexible. As considering this final year project desire to develop E-Bu Confinement Care Service (E-BuCCS) for CHA Beauty Home Spa’s business. The current business process of CHA Beauty Home Spa led to some issue such as timeconsuming, redundant booking and lost data. Hence, this study aims to make it easier for the user who will use it without needing to come to specific places and could save time on booking an appointment. This study aims to develop an effective CHA Beauty Home Spa system to improve its business process. This E-Bu Confinement Care Service (E-BuCCS) system function allows CHA Beauty Home Spa to be more organised because it is much more functional for the administrator to manage the database of user. The most effective approach where its convenience to every user, such as admin, staff, and customer